Genetic comorbidity between major depression and cardio‐metabolic traits, stratified by age at onset of major depression. Issue 6 (18th July 2020) - Hagenaars, Saskia P.; Coleman, Jonathan R. I.; Choi, Shing Wan; Gaspar, Héléna; Adams, Mark J.; Howard, David M.; Hodgson, Karen; Traylor, Matthew; Air, Tracy M.; Andlauer, Till F. M.; Arolt, Volker; Baune, Bernhard T.; et al.
Abstract: It is imperative to understand the specific and shared etiologies of major depression and cardio‐metabolic disease, as both traits are frequently comorbid and each represents a major burden to society. This study examined whether there is a genetic association between major depression and cardio‐metabolic traits and if this association is stratified by age at onset for major depression. Polygenic risk scores analysis and linkage disequilibrium score regression was performed to examine whether differences in shared genetic etiology exist between depression case control status ( N cases = 40, 940, N controls = 67, 532), earlier ( N = 15, 844), and later onset depression ( N = 15, 800) with body mass index, coronary artery disease, stroke, and type 2 diabetes in 11 data sets from the Psychiatric Genomics Consortium, Generation Scotland, and UK Biobank. All cardio‐metabolic polygenic risk scores were associated with depression status. Significant genetic correlations were found between depression and body mass index, coronary artery disease, and type 2 diabetes. Higher polygenic risk for body mass index, coronary artery disease, and type 2 diabetes was associated with both early and later onset depression, while higher polygenic risk for stroke was associated with later onset depression only. Significant genetic correlations were found between body mass index and later onset depression, and between coronary artery disease and both early and late onset depression. The phenotypic associations between major depression and cardio‐metabolic traits may partly reflect their overlapping genetic etiology irrespective of the age depression first presents.